2017
DOI: 10.1007/s12013-017-0796-3
|View full text |Cite
|
Sign up to set email alerts
|

Modified Metformin as a More Potent Anticancer Drug: Mitochondrial Inhibition, Redox Signaling, Antiproliferative Effects and Future EPR Studies

Abstract: Metformin, one of the most widely prescribed antidiabetic drugs in the world is being repurposed as a potential drug in cancer treatment. Epidemiological studies suggest that metformin exerts anticancer effects in diabetic patients with pancreatic cancer. However, at typical antidiabetic doses the bioavailability of metformin is presumably too low to exert antitumor effects. Thus, more potent analogs of metformin are needed in order to increase its anticancer efficacy. To this end, a new class of mitochondria-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Another successful antiproliferative strategy may be to increase in reactive oxygen species (ROS) production and subsequent induction of apoptosis [ 49 , 50 ]. It was also proposed for biguanides that their primary antiproliferative effect is manifested through increase in ROS production [ 21 , 23 ], which also holds true for the mitochondria-targeted analogs [ 51 ]. In this case, the mitochondrial ROS also interfered with redox signaling events.…”
Section: Resultsmentioning
confidence: 99%
“…Another successful antiproliferative strategy may be to increase in reactive oxygen species (ROS) production and subsequent induction of apoptosis [ 49 , 50 ]. It was also proposed for biguanides that their primary antiproliferative effect is manifested through increase in ROS production [ 21 , 23 ], which also holds true for the mitochondria-targeted analogs [ 51 ]. In this case, the mitochondrial ROS also interfered with redox signaling events.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, in intestine where CRC is located, at standard doses for diabetic patients, metformin could reach mM levels, which is most probably due to the high expression of OCTs in enterocytes ( Bailey et al, 2008 ). Of note, efforts have been made to augment the activity of metformin; by attaching a lipophilic substituent, inhibitory effect of metformin toward complex I is potentiated about 1000-fold ( Kalyanaraman et al, 2017 ). Secondly, it has been shown that cancer cells exhibiting higher mitochondrial respiratory activity are more sensitive to biguanide drugs ( Hsu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Modified from Ref. [87] . Reprinted from Cell Biochemistry and Biophysics, Modified Metformin as a More Potent Anticancer Drug: Mitochondrial Inhibition, Redox Signaling, Antiproliferative Effects and Future EPR Studies, 75, 2017, 311-7, B. Kalyanaraman, G. Cheng, M. Hardy, O. Ouari, A. Sikora, J. Zielonka, M.B.…”
Section: Monitoring Intracellular Fluorescence Derived From Redox Promentioning
confidence: 99%